A discrete approach for modelling backfill material in masonry arch bridges. (November 2019) - Sarhosis, Vasilis; Forgács, Tamás; Lemos, Jose V.
Highlights: A novel approach to represent cracking in backfill of masonry arch bridges proposed. Backfill is considered as an assemblage of densely packed discrete irregular particles. A fair to good agreement between the experimental and the numerical results was obtained. Initiation and propagation of cracking in soil is captured with the application of external load. The approach can be used to better understand the load distribution in masonry arch bridges. Abstract: Masonry arch bridges form a significant portion of the European transport infrastructure network. Many of these bridges are relatively old but still in service. Increasing vehicle loads and speeds have highlighted the need for reliable estimates of their service condition. Past research demonstrated that load-carrying capacity of a masonry arch bridge is a function of the soil response. However, today, the approaches used for the simulation of soil in masonry arch bridges are over-simplistic and most of them do not take into account the soil-structure interaction phenomena. This paper presents a novel modelling approach, based on the discrete element method, for the simulation of backfill material in masonry arch bridges. According to the method, bricks in the barrel vault are simulated as an assembly of distinct blocks separated by zero thickness interfaces at each mortar joint. Backfill is represented as an assemblage of densely packed discrete irregular deformable particles, here called "inner-backfill particles". A series of computational models were developed and their results are compared against full-scale experimental test results. A good agreement between the experimental and the numerical results was obtained which demonstrates the huge potential of this novel modelling approach. One of the major advantages of the proposed approach is its ability to simulate the initiation and propagation of cracking in the backfill and arch ring with the application of the external load. It is envisaged that the current modelling approach can be used by bridge assessment engineers for understanding soil pressures and load distribution on the backfill and arch ring and thus develop serviceability criteria for masonry arch bridges of their care.